The Campus Canopy, 1941-05-24 - The Campus Canopy, The Georgia State Woman's College (The Georgia State Woman's College, 1941)
The Campus Canopy, May 24, 1941. Vol. 7, No. 27. -- Final Issue -- 28th Commencement Week Begins June 2 -- Stuart Barnwell Delivers Baccalaureate Sermon -- Commencement Week -- Dean Hollis Eden Gives Commencement Address -- Philharmonic Will Feature Members In Two Programs -- Parham Will Give Recital, May 26th -- Graduates Express Sentiments Of Delight, Sorrow and Fright -- Exam Schedule For Spring -- Flash... -- Scoop... -- Tradition Upheld By Senior Class
Digitized from original print, Valdosta State University Archives and Special Collections, February 2, 2017.
Keywords: The Campus Canopy; The Georgia State Woman's College; GSWC; Valdosta State College; Valdosta State University; VSC; VSU; 1940s; 1941; Final Issue; Commencement Week